?LIPID STUDIES OF ANNONA SQUAMOSA (Biological Sciences - PJSIR, 1996)
The air dried seeds ofAnnona squamosa contain moisture 10.0%, oil 23.0% minerals 1.89% and proteins 24.05%. The fatty acid composition of light yellow coloured oil is C16:0 (13.51 %), C18.0 (10.40%), C18.1 (46.96%), CI 8:2 (25.89%), C I8:3 (1.39%) and an unknown acid 1.95% .The unsaponifiable is determined as sterols (25.1 %), alcohols (54.1 %) and hydrocarbons (20.8%). The hydrocarbons (C11-C31) and alcohols (C16-C18) have been separated, identified ad characterized by the application of thin layer and gas liquid chromatography.